The moderating role of family ecological factors (family size) on the relationships between family environment and emotional intelligence - Naghavi, Fataneh; Redzuan, Ma'rof (Marsland Press, 2012)
While a huge of literature indicates that family environment influence emotional intelligence, the family size as one of the important determinants which buffers this effect received little empirical attention. The current study investigated the moderating role of family size on the relationships between family environment and emotional intelligence among 234 early adolescents (girls and boys) in grades 2 and 3 of guidance schools of Tehran, Iran. Data were collected using the Emotional Quotient Inventory Youth Version (Bar- on EQ-i; YV, 2000) and the Moos and Moos Family Environment Scale. Results revealed that family environment fostered emotional intelligence in their early adolescents. Furthermore, the findings demonstrated that family size moderated the relationship between family environment and emotional intelligence. Specifically, early adolescents tended to indicate more emotional intelligence at higher levels of family environment when family have fewer members. These findings underscore the need for continued focus on the role of family size when assessing the links between family environment and early adolescent’s emotional intelligence. Researchers have demonstrated that in family functioning related to early adolescents’ emotions, family and their characters such as family size is very important in the lives at early adolescence.